Challenges in a large mixed drug overdose patient. (22nd June 2016) - Zhang, Paige; Austin, Emily; Thompson, Margaret; Lin, Steve
Abstract : A 39-year-old homeless man was found confused and incoherent after ingesting an estimated total of 200 tablets of various medications. He presented to the emergency department with delirium, tachycardia, clonus and hyperthermia of 38.0°C. His condition worsened rapidly with his temperature rising to 39.9°C despite active cooling. The patient was subsequently sedated, intubated, paralysed and admitted to the intensive care unit, where he remained for 38 days. His initial presentation of a large mixed drug overdose manifested as serotonin syndrome, which had a protracted course complicated by ethanol withdrawal. He eventually stabilised and was transferred to the general ward, and was subsequently discharged from hospital on day 47 with continuing psychiatric care. This case demonstrates the challenges and considerations in diagnosis and management of large mixed drug overdoses where multiple toxidromes overlap.